2009
DOI: 10.1159/000218358
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Intervention Leads to Better Sound Localization in Children with Bilateral Cochlear Implants

Abstract: We present sound localization results from 30 children with bilateral cochlear implants. All children received their implants sequentially, at ages from 6 months to 9 years for the first implant and 1.5–12 years for the second implant, with delays of 10 months to 9 years. Localization was measured in the sound field, with a broadband bell-ring presented from 1 of 9 loudspeakers positioned in the frontal horizontal plane. The majority of the children (63%) were able to localize this signal significantly better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
91
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 49 publications
(19 reference statements)
10
91
2
Order By: Relevance
“…This may indicate either that a longer duration of hearing loss leads to loss of the ability to access binaural cues, even when hearing is stimulated later on in life, or that these 2 subjects never completely developed binaural hearing. Similarly, in the study of Van Deun et al [21], the children who scored best on localization used hearing aids for 18 or more months before implantation or were first implanted before the age of 2. Steffens et al [18] suggest that initial binaural auditory experience is related to the high bilateral localization abilities of postmeningitic children reported in their study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This may indicate either that a longer duration of hearing loss leads to loss of the ability to access binaural cues, even when hearing is stimulated later on in life, or that these 2 subjects never completely developed binaural hearing. Similarly, in the study of Van Deun et al [21], the children who scored best on localization used hearing aids for 18 or more months before implantation or were first implanted before the age of 2. Steffens et al [18] suggest that initial binaural auditory experience is related to the high bilateral localization abilities of postmeningitic children reported in their study.…”
Section: Discussionmentioning
confidence: 97%
“…The authors, Bauer et al [17], suggested that this was related to the high degree of plasticity of the system, which allowed potential development of these binaural skills. A number of recent studies have confirmed and elaborated on children's potential to use bilateral CIs to achieve or recover binaural hearing advantages in speech perception and localization [18,19,20,21,22,23]. However, research by Peters et al [24] and Galvin et al [25,26,27] has reported more modest benefits for localization, if any.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on their hearing history and speech processors are given in Table 1. The children participated in previous research on sound localization (Van Deun et al 2010a) and single-channel binaural masking level differences ) and their IDs are similar to the ones used in those studies. Children were tested at their home; adults were tested at the hearing center of the Medical University of Hannover, Germany.…”
Section: Subjectsmentioning
confidence: 99%
“…The benefits of bilateral implantation in children are well documented in terms of improved localization [46][47][48] and enhanced speech recognition in quiet [49,50] and in noise [46,51,52] when compared to listening with a unilateral CI. Also recently confirmed, children with bilateral CIs have significantly better language outcomes compared to children with unilateral CIs [45,53].…”
Section: Introductionmentioning
confidence: 99%